Agro-Biotechnology: A Tool For Reducing Hunger and Poverty - Rathour, Rajat Satender; Agarwal, Kartik (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2018)
World poverty and hunger is a major concern of public health. Several methods are being adopted to overcome this problem. Science and technology have been able to make several major contributions to it. But one discipline, though equally profitable in form of results has been sidetracked so far. Agricultural biotechnology can offer various solutions which can help with eradicating the problem of not only hunger and poverty but also malnutrition and undernourishment. Thus with the growing population, the need to further develop this discipline is great.